The pelagic Complex in the North East Atlantic Ocean : Challenges and possibilities in the pelagic sector – looking towards the future (Copenhagen : Nordic Council of Ministers, 2011)
The Pelagic Complex conference was the major event in the Faroese Chairmanship of the Nordic Fisheries Cooperation 2010. The overall goal of the conference was to facilitate a scientifically-based and politically relevant discussion on the future of the pelagic fisheries in the North East Atlantic Ocean.This Proceedings presents an overview of the presentations and discussions that comprised the conference. The theme of the conference still remains politically contentious and the goal of creating a platform for joint dialogue on the future of the pelagic fisheries in the region is more relevant than ever and should serve as an excellent example for future activities designed to foster dialogue and renewed collaboration.